Learning Node.js for mobile application development : make use of Node.js to develop of a simple yet scalable cross-platform mobile application - Buttigieg, Stefan (Community experience distilled., 2015)
Make use of Node.js to learn the development of a simple yet scalable cross-platform mobile application About This Book Use Node.js to satisfy the core backend requirements of modern apps, including user management, security, data access, and real-time data communication Build practical real-world mobile applications, which will give you the necessary knowledge to build your very own mobile solutions Step-by-step development of projects using Ionic Framework as the frontend and Node.js for the backend supported by a MongoDB database Who This Book Is For This book is intended for web developers of all levels of expertise who want to deep dive into cross-platform mobile application development without going through the pains of understanding the languages and native frameworks that form an integral part of developing for different mobile platforms. This book is also for you if you are a developer who wants to capitalize on the MobileFirst strategy and so are going to use JavaScript for your complete stack. What You Will Learn Develop an API from scratch Set up a MongoDB Database as part of your mobile application backend Deploy a cross-platform mobile application from the command line Incorporate features within your mobile application that use native phone features such as a gyroscope, GPS, and accelerometer Implement mobile applications that use web-enabled APIs Build a mobile application with real-time chat messaging features Develop a secure mobile application that is capable of functioning with real-time data In Detail Node.js is a massively popular JavaScript library that lets you use JavaScript to easily program scalable network applications and web services. People approaching Node.js for the first time are often attracted by its efficiency, scalability, and the fact that it's based on JavaScript, the language of the Web, which means that developers can use the same language to write backend code. Also, it's increasingly being seen as a "modern" replacement for PHP in web development, which relies on fast-paced data exchange. The growing community and the large amount of available modules makes Node.js one of the most attractive development environments. This book takes a step-wise and incremental approach toward developing cross-platform mobile technologies using existing web technologies. This will allow you to truly understand and become proficient in developing cross-platform mobile applications with Node.js, Ionic Framework, and Mon...